2016
DOI: 10.1111/1748-5967.12150
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macroinvertebrate biodiversity improved with irrigation ponds linked to a rice paddy field

Abstract: Traditionally, many irrigation ponds supplied water to paddy fields, but most of these ponds have disappeared through improvements in irrigation systems. The aim of this study was to assess the ecological functions (especially biodiversity conservation) of irrigation ponds by using benthic macroinvertebrates that inhabit paddy fields. This study was conducted in Hwaseong‐si, Yesan‐gun, Hongseong‐gun, Uljin‐gun and Damyang‐gun, Korea. Benthic macroinvertebrates were collected using a quadrat sampler from August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…3). Choe et al (2016) suggested that the restoration of traditional irrigation ponds that have disappeared through improvements in irrigation systems is an effective method for maintaining and enhancing the biodiversity in the paddy ecosystem. However, aquatic invertebrate communities in non-land consolidated paddy fields were divided according to their geographical location, such as the eastern region (cluster IIa), western region (cluster IIb), and northern region (cluster IIc).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Choe et al (2016) suggested that the restoration of traditional irrigation ponds that have disappeared through improvements in irrigation systems is an effective method for maintaining and enhancing the biodiversity in the paddy ecosystem. However, aquatic invertebrate communities in non-land consolidated paddy fields were divided according to their geographical location, such as the eastern region (cluster IIa), western region (cluster IIb), and northern region (cluster IIc).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that land consolidation and modernization of irrigation system have destroyed the habitats of aquatic invertebrates such as small irrigation ponds and soil ditches, resulting in a decrease in diversity of aquatic invertebrates Kim et al 2012;Sato & Maruyama 1996;Azuma & Takeuchi 1999). Choe et al (2016) suggested that the restoration of traditional irrigation ponds that have disappeared through improvements in irrigation systems is an effective method for maintaining and enhancing the biodiversity in the paddy ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The eutrophication of these ponds can be problematic for the ecosystems and human health. Different studies show that these ponds have an important effect on biodiversity, such as providing refuges for endangered species that live in freshwater bodies [4][5][6]. Biodiversity has essential advantages in human and agricultural environments.…”
Section: Introductionmentioning
confidence: 99%
“…S1). A dumbeong enhances farm biodiversity by providing habitat for various organisms (Kim et al, 2011;Choe et al, 2013Choe et al, , 2016. However, with the adoption of mechanized irrigation and agricultural intensification practices, dumbeongs are coming into disuse (Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%